2005
DOI: 10.1086/430428
|View full text |Cite
|
Sign up to set email alerts
|

Optical Photometry and Spectroscopy of the Suspected "Cool Algol" AV Delphini: Determination of the Physical Properties

Abstract: We present new spectroscopic and BVRI photometric observations of the double-lined eclipsing binary AV Del ( period ¼ 3:85 days) conducted over six observing seasons. A detailed radial velocity and light-curve analysis of the optical data shows the system to be most likely semidetached, with the less massive and cooler star filling its Roche lobe. The system is probably a member of the rare class of ''cool Algol'' systems, which are distinguished from the ''classical'' Algol systems in that the mass-gaining co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 23 publications
(29 reference statements)
1
18
0
Order By: Relevance
“…Initially, solutions were obtained assuming l 3 6 ¼ 0.0, but this assumption never resulted in satisfactory fits to the observations. Mader et al (2005) calculated a linear ephemeris:…”
Section: Assumptionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Initially, solutions were obtained assuming l 3 6 ¼ 0.0, but this assumption never resulted in satisfactory fits to the observations. Mader et al (2005) calculated a linear ephemeris:…”
Section: Assumptionsmentioning
confidence: 99%
“…On the other hand, the R filter observations of Mader et al (2005) were considered for the solutions since, as shown in Table 2, the accuracy of the results for this filter is greater than for the others.…”
Section: Shellspec Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Now that we understand the influence of various parameters on the emerging light curve, we can proceed to fit the real light curve of AV Del. We used the photometric data reported by Mader et al (2005) for analysis via the SHELLSPEC code. A detailed study of these data is published in Ghoreyshi et al (2011), in which an analysis of the photometric and radial-velocity data of the system by using both Wilson-Devinney code (Wilson & Devinney 1971;Wilson 1979Wilson , 1990) and the SHELLSPEC code performed.…”
Section: Changes To Light Curve From Varying Model Parametersmentioning
confidence: 99%
“…And please wave goodbye to the following sorts of binary system, since we will not mention them again, at least until Ap06-Cool Algols (Mader 2005 on AV Del, the 7th with an orbit, the first having come from Popper 1976). Also Algols with superhumps, which, like CV superhumps, are caused by a beat frequency between the orbit and disk precession frequencies (Retter et al 2005).…”
Section: Binary Starsmentioning
confidence: 99%